LAW ENFORCEMENT AGAINST PERPETRATORS OF CATEGORY I NARCOTICS CRIMES IN THE JURISDICTION OF THE ROKAN HILIR DISTRICT COURT - Sinaga, Richard; Harahap, Irawan; Kadaryanto, Bagio (EKSEKUSI, 2025)
ABSTRACT Article 112 paragraph (1) and paragraph (2) Jo. Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics regulates the minimum criminal threat of 4 years and 5 years. The purpose of the study To analyze law enforcement against perpetrators of class I Narcotics crimes at the Rokan Hilir District Court based on the regulation; To analyze obstacles and efforts to overcome them. The research method is sociological legal research with a legislative, case and analytical approach; the research location is the Rokan Hilir District Court; population and samples from relevant sources; data sources are primary, secondary and tertiary; data collection techniques are observation, non-structural interviews and document/library studies; data analysis is qualitative with inductive conclusions. The results of the study are that law enforcement at the Rokan Hilir Court has not been implemented properly. The conclusion is First, law enforcement against perpetrators of Class I Narcotics crimes in the Court based on regulations has not been running well where judges impose sentences below the minimum threat provisions in the Article for perpetrators of methamphetamine narcotics crimes in 2022 and 2023. Second, obstacles come from legislative factors; law enforcement officers; and the community (defendants and mitigating witnesses). Efforts to overcome this are Legislative factors, namely the judge's decision provides justice, benefits and legal certainty for the wider community; apply the rules carefully and appropriately; judges apply them to defendants who meet the criteria in the Circular of the Supreme Court; The government amends Law Number 35 of 2009 concerning Narcotics because in certain circumstances it is no longer in accordance with the needs of law enforcement; Judges apply the law based on the substance of Law Number 35 of 2009 concerning Narcotics. Law enforcement factors, namely judges are more careful and do not have certain interests and are in accordance with the examination concept in implementing Letter A number 1 of the Supreme Court Circular Letter Number 02 of 2015; Public Prosecutors are more careful and thorough in preparing the indictment and avoiding certain interests and then taking legal action. Community factors, namely the defendant and mitigating sanctions tell the truth in court; the judge's consideration in imposing a light sentence is truly in accordance with the conditions of the defendant when examined in court; The defendant can present mitigating witnesses.Keywords: Methamphetamine, Judge's verdict, Rokan Hilir ABSTRAK Pasal 112 ayat (1) maupun ayat (2)  Jo. Pasal 132 ayat (1) Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika mengatur ancaman pidana minimum yaitu 4 tahun dan 5 tahun. Tujuan penelitian Untuk menganalisis penegakan hukum terhadap pelaku tindak pidana Narkotika golongan I di Pengadilan Negeri Rokan Hilir berdasarkan regulasi tersebut; Untuk menganalisis hambatan dan upaya mengatasinya. Metode penelitiaan ialah penelitian hukum sosiologis dengan pendekatan perundang–undangan, kasus dananalitis; lokasi penelitian ialah Pengadilan Negeri Rokan Hilir; populasi dan sampel dari narasumber relevan; sumber data ialah primer, sekunder dan tersier; teknik pengumpulan data ialah observasi, wawancara non struktural dan studi dokumen/ kepustakaan; analisis data ialah kualitatif dengan kesimpulan induktif.  Hasil penelitiannya penegakan hukumnya di Pengadilan Rokan Hilir belum terlaksana dengan baik. Kesimpulannya ialah Pertama, Penegakan hukum terhadap pelaku tindak pidana Narkotika Golongan I di Pengadilan tersebut berdasarkan regulasi belum berjalan dengan baik dimana hakim menjatuhkan pidana dibawah ketentuan ancaman minimum dalam Pasal tersebut bagi pelaku tindak pidana narkotika jenis shabu pada tahun 2022 dan 2023. Kedua, hambatan berasal dari faktor perundang-undangan; aparat penegak hukum; dan masyarakat (terdakwa dan saksi yang meringankan). Upaya mengatasinya ialah Faktor perundang-undangan, yaitu putusan hakim memberikan, keadilan, kemanfaatan dan kepastian hukum bagi masyarakat luas; menerapkan aturan tersebut dengan cermat dan tepat; hakim menerapkannya terhadap terdakwa yang memenuhi kriteria dalam Surat Edaran Mahkamah Agung tersebut; Pemerintah melakukan perubahan Undang–Undang Nomor 35 Tahun 2009 tentang Narkotika karena dalam keadaan tertentu tidak sesuai lagi dengan kebutuhan penegakan hukum; Hakim menerapkan hukum berlandaskan pada substani Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika. Faktor aparat penegak hukum, yaitu hakim lebih cermat dan tidak punya kepentingan tertentu serta sesuai dengan konsep eksaminasi dalam menerapkan Huruf A angka 1 Surat Edaran Mahkamah Agung Nomor 02 Tahun 2015; Jaksa Penuntut Umum lebih cermat dan teliti menyusun surat dakwaan serta menghindari adanya kepentingan tertentu kemudian melakukan upaya hukum. Faktor masyarakat, yaitu terdakwa dan sanksi yang meringankan berkata jujur di persidangan; pertimbangan hakim dalam menjatuhkan vonis yang ringan memang benar-benar sesuai dengan kondisi-kondisi terdakwa saat dilakukan pemeriksaan di persidangan; Terdakwa dapat menghadirkan saksi yang meringankan.Kata Kunci: Metamfetamina, Putusan, Rokan Hilir